Numerical analysis of mechanical safety parameters of Congress Hall building in Chelyabinsk - Alexander M. Belostotsky; Pavel A. Akimov; Dmitry S. Dmitriev; Andrey S. Pavlov; Yulia N. Dyadchenko; Alexander I. Nagibovich (Structural Mechanics of Engineering Constructions and Buildings, 2019)
Aims of research. The article is devoted to actual problems of computational analysis of stress-strain state, strength and stability of load-bearing structures with allowance for the main and special combinations of loads and impacts, comparison of the results of alternative structural analysis of unique cultural and business complex “Congress Hall” in Chelyabinsk. The natural conditions of the area of location of this object and main load-bearing structures of the object are described. Besides, characteristic and design loads, their combinations, formulation of objectives of computational research and methods of solution are presented. Methods. Space discretization and solution of the corresponding problems of mathematical (numerical) and computer modelling of the considering unique building were carried out with the use of finite element method. Detailed finite element models of the coupled system “combined foundation - loadbearing structures” and its fragments (subsystems) were developed and verified. They adequately reflect geometric-stiffness, inertial and load parameters of the object and the resulting stress-strain state. Progressive collapse analysis are under consideration as well. Licensed, certified and verified (by the Russian Academy of Architecture and Construction Sciences) finite element software package “ANSYS Mechanical” was used. Results. The resulting parameters of stress-strain state, strength and dynamics of load-bearing structures of the building with allowance for design (in accordance with design codes) combinations of vertical and wind loads are considered. Besides, information about results of progressive collapse analysis is presented. Thus, a reasonable conclusion is made about the reliability of the criterion parameters of strength, stability and dynamics of the load-bearing structures of the object.